The Community Empowerment through Child Care Groups to Prevent the Dangers of Using Gadgets for School Age Children During the COVID-19 Pandemicin Baratan Village Jember Regency: Pemberdayaan Masyarakat melalui Kelompok Peduli Anak Sebagai Prevensi Bahaya Penggunaan Gadget Anak Usia Sekolah di Masa Pandemi Covid-19 Kelurahan Baratan Kabupaten Jember (JURNAL UNEJ, 2024)
The impact of the COVID-19 pandemic on health during the work from home policy has affected various age groups from babies to the elderly, one of which is school age children. The learning from home (BDR) process makes school-aged children interact more with gadgets because learning is done online. It is feared that increasing the intensity of ganget use will also increase the prevalence of the risk of attention deficit disorder and hyperactivity. The aim of this service is to form a child care group focused on dealing with the problem of gadget use in children as a prevention of the dangers of using gadgets for school-aged children during the COVID-19 pandemic. The method of implementing this service involves several stages of activities, namely identifying partner problems, designing service programs, implementing service programs, and monitoring, evaluating, and planning follow-up from the formation of child care groups. The targets for implementing the Assisted Village Service program are family welfare empowerment (PKK) administrators, dasawasma administrators, local neighborhood association (RT) administrators, and cadres.